PENGARUH PERSEPSI DAN MINAT SISWA TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Usifa, Inggrid Mariana; Simarmata, Justin Eduardo; Kehi, Yohanes Jefrianus (De Fermat : Jurnal Pendidikan Matematika, 2026)
Low mathematics learning outcomes among students remain a concern at SMP Negeri Oenenu and are presumed to be influenced by internal factors, particularly students’ perceptions of mathematics learning and their learning interest. This study aims to examine the effect of students’ perceptions and learning interest on mathematics learning outcomes, both partially and simultaneously, among eighth-grade students at SMP Negeri Oenenu. This study employed a quantitative approach using an ex post facto research design. The population consisted of 122 eighth-grade students, with 92 students selected as the sample. The data were analyzed using inferential statistics through multiple linear regression analysis. The results of the analysis yielded the regression equation , indicating that students’ perceptions have a negative relationship with mathematics learning outcomes, while learning interest has a positive relationship with mathematics learning outcomes. Furthermore, hypothesis testing shows that students’ perceptions significantly influence mathematics learning outcomes, learning interest significantly influences mathematics learning outcomes, and both variables simultaneously have a significant effect on the mathematics learning outcomes of eighth-grade students at SMP Negeri Oenenu.